Metacognitive Approach to Smoking Dependency: A Review of the Current Literature - Alma-Uzuntuna, Leyla; Yılmaz, Adviye Esin (Addicta: The Turkish Journal on Addictions, 2020)
The use of tobacco and tobacco products is a leading cause of preventable health problems and results in many deaths. Thus, a better understanding of cigarette use and the mechanisms of addiction would advance the literature. This study aims to explain the addiction to smoking in accordance with the metacognitive approach, which has a current and innovator point of view, and provides evidence that the metacognitive approach might be a novel treatment for smoking dependency. The metacognitive approach has been used to understand and treat resistant psychological disorders, provide novel understanding regarding addiction mechanisms, and present a treatment approach that explains the following factors: initiating, perpetuating, and smoking dependency relapse. The findings of the few studies that have investigated the role of metacognitions in the mechanisms of cigarette use and quitting smoking are promising to demonstrate evidence of the validity of the metacognitive approach. According to the findings, possible interventions to improve policies are discussed. Sigara Bağımlılığına Üstbilişsel Yaklaşım: Güncel Duruma İlişkin Bir Gözden Geçirme Tütün ve tütün ürünleri, önlenebilir sağlık sorunlarının başında geliyor olmakla birlikte çok sayıda kişinin hayatını kaybetmesine neden olmaktadır. Sigara kullanımını caydırıcı politikalara rağmen, sigara bağımlılık oranlarının halen yüksek olması, sigara kullanımını ve bağımlılık mekanizmasını daha iyi anlamayı gerektirmektedir. Bu çalışmada, sigara bağımlılığının güncel ve yenilikçi bir bakış açısı olan üstbilişsel yaklaşım çerçevesinden açıklanması amaçlanmış ve sigara bağımlılığının tedavisinde üstbilişsel yaklaşımın farklı bir pencere açıyor olabileceğine yönelik bilgiler aktarılmıştır. Dirençli psikolojik bozukları daha iyi anlamak ve tedavi etmek amacıyla ortaya çıkan üstbilişsel yaklaşım, bağımlılık mekanizmasına da açıklama getirmekte ve bağımlılığın başlamasına, sürmesine ve nüks etmesine katkıda bulunan faktörleri kapsayan bir tedavi yaklaşımı sunmaktadır. Sigara kullanma ve sigara bırakma mekanizmalarında rol oynayan üstbilişleri inceleyen az sayıdaki araştırma bulguları, üstbilişsel yaklaşımın geçerliğine yönelik kanıtlar sunmaktadır. Bu bulgular çerçevesinde, üstbilişsel yaklaşımın gelecekte yön verebileceği müdahaleler tartışılmıştır. To